O papel do sujeito face à imagem. Interpretações estruturo-fenomenológicas: o caso de estudo das Pinturas murais de São Francisco de Bragança - Inês Afonso Lopes (Medievalista)
The historiography and its role concerning the art and images, throughout the last decades are adopting as the main way of investigation the so called historical anthropology, as heritage of the works from writers like Marc Bloch, Fernand Braudel e Jacques Le Goff. Notwithstanding, that historic anthropology has been targeted from several criticisms, owing the fact that often it is only focused on the structural anthropology rather than watching the role of its agents/actors. Upon the axis of convergence of such analytical dimensions (structure and phenomenology), the new guiding lines of historical anthropology, start to find a balance, which allows the development of a greater epistemological richness.From the use of the case of study of the murals of S. Francisco de Bragança Convent, we intend to explore not only the role that the historical circumstances played on its achievement, but also how the involved people possibly understood the same.Therefore, using that example, we intend to demonstrate that material artwork only find its meaning when we also look after the people actually involved, who really had interacted with it.